Three Toxoplasma gondii Dense Granule Proteins Are Required for Induction of Lewis Rat Macrophage Pyroptosis - Wang, Yifan (mBio, 2019)
Upon invasion of Lewis rat macrophages, Toxoplasma rapidly induces programmed cell death (pyroptosis), which prevents Toxoplasma replication, possibly explaining the resistance of the Lewis rat to Toxoplasma. Using a chemical mutagenesis screen, we identified Toxoplasma mutants that no longer induced pyroptosis. Whole-genome sequencing led to the identification of three Toxoplasma parasitophorous vacuole-localized dense granule proteins, GRA35, GRA42, and GRA43, that are individually required for induction of Lewis rat macrophage pyroptosis. Macrophage infection with Δgra35, Δgra42, and Δgra43 parasites led to greatly reduced cell death rates and enhanced parasite replication. Lewis rat macrophages infected with parasites containing a single, double, or triple deletion of these GRAs showed similar levels of cell viability, suggesting that the three GRAs function in the same pathway. Deletion of GRA42 or GRA43 resulted in GRA35 (and other GRAs) being retained inside the parasitophorous vacuole instead of being localized to the parasitophorous vacuole membrane. Despite having greatly enhanced replication in Lewis rat macrophages in vitro, Δgra35, Δgra42, and Δgra43 parasites did not establish a chronic infection in Lewis rats. Toxoplasma did not induce F344 rat macrophage pyroptosis, but F344 rats infected with Δgra35, Δgra42, and Δgra43 parasites had reduced cyst numbers. Thus, these GRAs determined parasite in vivo fitness in F344 rats. Overall, our data suggest that these three Toxoplasma dense granule proteins play a critical role in establishing a chronic infection in vivo, independently of their role in mediating macrophage pyroptosis, likely due to their importance in regulating protein localization to the parasitophorous vacuole membrane.